Seasonal variation in the diet of Lontra longicaudis in the Paraná River basin, Argentina - Vezzosi, Raúl Ignacio (2014)
We studied the Neotropical otter ( Lontra longicaudis ) seasonal diet variations in the middle Paran á River valley, in central-northern Argentina, at the southern limit of its global range. We recorded 745 prey items in 320 scats collected over the course of 1 year in a tributary stream of the Paran á River. Fish, crustaceans, mammals, and insects were the most important items in frequency of occurrence among items. Other items, like mollusks, birds, amphibians, and reptilians were presented in low frequency in all seasons. We recorded seasonal variation in the frequency of the principal categories items: fish, mammals, crustaceans, and insects and in reptilian that had low frequency. Although fish were the most common items consumed by the otter, other groups such as crustaceans, mammals, and insects, were also important in the diet of the Neotropical otter throughout the seasons. Mammals and insects showed a higher frequency in the Neotropical otter diet in our study than in Brazil, Mexico, and even northern Argentina. We noted a marked variation throughout the Neotropical region in the niche breadth indices among studies of Neotropical otter ’ s diet. The Shannon H ′ diversity index showed a higher value in our study than in most of previous diet analyses of this species.